Architectural, Civil, and Infrastructure Engineering in View of Sustainability - Kapliński, Oleg; Dong, Lili; Bonenberg, Agata; Bonenberg, Wojciech (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the position of sustainability in engineering and points to the multidimensionality of the issue. Architecture, civil and engineering issues are main themes of discussion, with special attention to research and design. Attention is focused on four thematic groups: energy (including energy harvesting), economy (including building circularity), pro-health activities, and design.